2022
DOI: 10.1002/cphc.202200769
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects in Gas‐phase C−H Activation

Abstract: The gas‐phase clusters reaction permits addressing fundamental aspects of the challenges related to C−H activation. The size effect plays a key role in the activation processes as it may substantially affect both the reactivity and selectivity. In this paper, we reviewed the size effect related to the hydrocarbon oxidation by early transition metal oxides and main group metal oxides, methane activation mediated by late transition metals. Based on mass‐spectrometry experiments in conjunction with quantum chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…Metal–metal bonds are ubiquitous in atomic clusters composed of multiple metal atoms, which provide an excellent platform to explore the critical role of metal–metal interaction displayed in activation and transformation of inert molecules. With the development of experimental techniques (e.g., laser vaporization) for preparation of metal clusters in isolated gas-phase environments, the reactivity of transition metal clusters toward methane has gained great attention in the area of cluster science since 1980s. A considerable number of bare noble metal (NM) clusters in different charge states (e.g., Pd n ≤23 , Pt n ≤24 ± , Rh n ≤10 ) were observed to dehydrogenate methane at room temperature. Available mechanistic studies revealed that single NM atoms generally serve as reactive sites to bring about C–H activation.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–metal bonds are ubiquitous in atomic clusters composed of multiple metal atoms, which provide an excellent platform to explore the critical role of metal–metal interaction displayed in activation and transformation of inert molecules. With the development of experimental techniques (e.g., laser vaporization) for preparation of metal clusters in isolated gas-phase environments, the reactivity of transition metal clusters toward methane has gained great attention in the area of cluster science since 1980s. A considerable number of bare noble metal (NM) clusters in different charge states (e.g., Pd n ≤23 , Pt n ≤24 ± , Rh n ≤10 ) were observed to dehydrogenate methane at room temperature. Available mechanistic studies revealed that single NM atoms generally serve as reactive sites to bring about C–H activation.…”
Section: Introductionmentioning
confidence: 99%
“…Distinctly, the acetonitrile (CH 3 CN) ligand was found to switch the mechanism of methane activation mediated by diatomic cation ZnO + , ultimately resulting in the improvement of product selectivity at the expense of activity. In sharp contrast with the extensively investigated single-metal systems, the preparation and reactivity study of the ligated or “supported” metal clusters, which represent important classes of heterogeneous ,, catalysts for many reactions, were rarely investigated in the gas phase, despite that a considerable number of free metal clusters and metal compound (oxide, carbide, nitride, and boride) clusters being capable of activation and functionalization of methane under mild conditions have been reported in the literature. ,, , …”
mentioning
confidence: 99%